The Impact of International Conflicts on the Development of the Maritime Tourism Sector in Southeast Asia - Salsabila Kamaluddin; Seniwati Seniwati (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
International conflicts significantly impact maritime tourism development in Southeast Asia, a region rich in natural marine beauty and essential to the regional economy. Destructive international disputes, including geopolitical tensions and naval security threats, can significantly disrupt the regional stability on which tourism is built. Although maritime tourism in Southeast Asia continues to show post-pandemic growth, conflict risk remains a significant challenge that could affect traveler confidence and hinder the sector's contribution to regional GDP. The impact of international conflicts on the development of maritime tourism in Southeast Asia is analyzed in this research using a qualitative approach and literature study method. Journals, articles, and reports were reviewed to understand how geopolitical tensions and maritime security threats affect the tourism sector. The study utilizes conflict theory to explain the dynamics of conflict escalation and the application of resolution efforts in this context. Therefore, the potential disruption of maritime tourism development by ongoing conflicts in the Southeast Asian region is highlighted. The sustainability of the industry relies on security stability, and regional cooperation is crucial in mitigating the negative impact of conflict on the economic sector.